Ultrawideband, high performance, cavity-backed Archimedean spiral antenna with Phelan balun for direction finding and radar warning receiver applications - Akkaya, Eren; Gunes, Filiz (WILEY, 2021)
This article presents a 2 to 18 GHz absorber-loaded cavity-backed (AL-CB) two-arm Archimedean spiral antenna fed by a 186 omega Phelan balun for direction finding (DF) and radar warning receiver (RWR) applications. The balun's cross-sectional area diameter at the antenna feeding region is less than the diameter of the active region ring at 18 GHz. This feature provides a lower axial-ratio (AR) and wobble-on-wave (WoW) at higher operating frequencies and far theta angles and distinguishes the proposed AL-CB spiral antenna from its counterparts and commercial off-the-shelf (COTS) products. The proposed antenna is 60 mm in diameter and 50 mm in height. The voltage standing wave ratio is typically less than 2 (max. 2.6), which is within 2 to 18 GHz frequency range, and the AR is less than 1 dB with a peak of 3.1 dB in off-axis < 60 degrees. The WoW is less than 2 dB in off-axis < 60 degrees. This study's simulation and measurements both demonstrate the ultrawideband (UWB) with 1:9 bandwidth, unidirectional, symmetric, and circularly polarized radiation characteristics of the proposed antenna for DF and RWR applications.
Keywords: Archimedean spiral antenna; axial ratio; balun; circular polarization; pattern symmetry; BAND; DESIGN; Computer Science; Engineering